2015
DOI: 10.1039/c5nr00772k
|View full text |Cite
|
Sign up to set email alerts
|

Correlated structural-optical study of single nanocrystals in a gap-bar antenna: effects of plasmonics on excitonic recombination pathways

Abstract: We performed time-correlated single-photon counting experiments on individual silica coated CdSe/CdS core/thick-shell nanocrystal quantum dots (a.k.a., giant NQDs [g-NQDs]), placed on the plasmonic gap-bar antennas. Optical properties were directly correlated with the scanning electron microscopy (SEM) images of g-NQD-plasmonic antenna coupled structures. The structures, in which the g-NQDs are located in the gap of the antenna, afford a coupling with up to 9.6 fold enhancement of radiative recombination rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 42 publications
8
39
1
Order By: Relevance
“…The fits to two single g‐NQDs that are coupled to the antennas (Figure b blue points and Figure S6a, Supporting Information) also give A values of 8.6 and 9.5, respectively, indicating that coupling to the antennas does not provide any enhancement to σ at the laser excitation wavelength of 405 nm. This finding is consistent with the results of our simulated and experimentally measured light scattering spectra, both of which show no enhancement at 405 nm …”
supporting
confidence: 93%
See 1 more Smart Citation
“…The fits to two single g‐NQDs that are coupled to the antennas (Figure b blue points and Figure S6a, Supporting Information) also give A values of 8.6 and 9.5, respectively, indicating that coupling to the antennas does not provide any enhancement to σ at the laser excitation wavelength of 405 nm. This finding is consistent with the results of our simulated and experimentally measured light scattering spectra, both of which show no enhancement at 405 nm …”
supporting
confidence: 93%
“…The dimensions are selected to achieve a plasmon resonance that overlaps directly on PL emission band of the QDs (640 nm). This overlap, confirmed by the measured scattering spectra, ensures strong enhancement to the dipole–dipole interaction. While any antenna in resonances with the emission of QDs can in principle be utilized, we chose this geometry to make placement of nanocrystal quantum dots (NQDs) easier.…”
supporting
confidence: 64%
“…PL intensity-time traces, PL decay curves, and 2 nd order photon correlation functions providing a measure on relative emission efficiency of bi-exciton emission process 24 25 26 27 are compared with those of referenced g-NQDs spread on the glass substrates. They are also compared with those measured on g-NQDs placed in the center of parallel gap-bar antennas utilizing two-step e-beam lithography (see Supporting Information S2 ) 17 24 . The gap-bar antennas are also designed to be in resonance with the emission band of the g-NQDs.…”
Section: Resultsmentioning
confidence: 99%
“…All these applications, however, necessitate the ability to precisely position or align the quantum emitters with respect to the antennas so that strong coupling between them can be induced. In the past few years, several bottom-up self-assembly approaches 15 16 as well as top-down electron beam lithography-based approaches 11 17 have been developed to realize the desired alignments. Notably, single nanocrystal quantum dots (NQDs) have been incorporated into 14–30 nm gaps of dimer nanoantennas by using a two-step e-beam lithography method 11 .…”
mentioning
confidence: 99%
“…For example, it was shown that when QDs were attached to the plasmonic gap-bar antennas, the EX radiative recombination rate increased, but this process did not affect the BX QY. [37] Thus, the effects of PNPs on BX PL are ambiguous. On the one hand, the EX QY can be reduced by metal-induced quenching; on the other hand, BX QY can be enhanced by the Purcell effect, and at the same time, plasmon-induced local electromagnetic field can affect the photon statistics of higher-order excitonic quasiparticles.…”
Section: Introductionmentioning
confidence: 99%